2016
DOI: 10.5432/jjpehss.16007
|View full text |Cite
|
Sign up to set email alerts
|

The factorial concept of inferiority complexes and their relationship to students' personal characteristics regarding physical education

Abstract: : The factorial concept of inferiority complexes and their relationship to students' personal characteristics regarding physical education. Japan J. Phys. Educ. Hlth. Sport Sci. 61: 663 680, December, 2016 AbstractWe investigated the factorial concept and features of Japanese elementary and junior high school students' inferiority complexes in relation to physical education. Fifth and sixth graders (n= 341) and junior high school students (n=336) completed 3 questionnaires: one created for this study and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The positive emotions generated by experiences of success are considered essential for students to adjust to PE classes. In contrast, students who are not good at sports are less likely to experience the positive emotions associated with successful experiences and are more likely to form maladjustments (Sasaki and Suko, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive emotions generated by experiences of success are considered essential for students to adjust to PE classes. In contrast, students who are not good at sports are less likely to experience the positive emotions associated with successful experiences and are more likely to form maladjustments (Sasaki and Suko, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This is because positive and negative feelings and approaches toward class are believed to have positive and negative effects on a student's adjustment. Indeed, previous studies have shown that active participation in PE classes promotes adjustment (Suzaki and Sugiyama, 2015) and that students who dislike PE classes are more likely to have an aversive attitude toward PE classes (Sasaki and Suko, 2016).…”
Section: Survey Contents (1) the Cover Sheetmentioning
confidence: 99%
“…The second point to consider is the effect of an inferiority complex with regard to feelings of disgust, avoidance behavior, and passive recognition toward physical education. Sasaki and Suko (2016) revealed that girls tend to experience a greater inferiority complex in physical education at upper levels of elementary school than boys do. This suggests that girls are more likely to develop an inferior complex in physical education, which reduces their opportunities to attain successes and entertain a sense of achievement through exercise and sports.…”
Section: Regarding Grade and Sex Differencesmentioning
confidence: 99%